O6 How to map the invisible: using simulation to find a trail. (November 2018) - Karydi, Konstantina Ilia; Jones, Val; Broom, Christopher; Corns, Jennifer; Snelgrove, Huon; Zoumprouli, Argyro
Abstract : Introduction: Clinical pathways are operational tools for implementing best practice. They form a bridge between available evidence and clinical practice and are associated with reduced in-hospital complications. 1 Stroke is the most common serious neurological disease and mechanical thrombectomy is recommended as a treatment for patients with acute ischaemic stroke due to large vessel occlusion. 2 The thrombectomy pathway presents unique challenges as it requires precise and coordinated work among different ad-hoc professional teams. All these teams interact with patients, relatives, equipment, technology and at the same time adhere to policies and guidelines. These interactions combined with time pressure contribute to tensions, conflict of individual tasks, adaptations, workarounds and bottlenecks. The aim of the study was to explore pathway development and implementation as part of quality improvement in St George's Hospital (SGH). Methods: We used a mixed-methods approach to gather data: focus–group discussions and interviews, exploring staff perceptions regarding their role and clinical processes that impact on patient safety, interdisciplinary mobile in–situ simulation as a tool for collective envisioning of the pathway literature review, and hospital data. We drew on conceptual models from human factors, ergonomics and activity theory to organise and interpret our findings. 3 Outcomes: In-situ simulation revealed to us a negative image of the pathway and its characteristics. Visibility of the pathway to different staff was variable: well-trodden to some, faint or even invisible to others. Team simulations provided spaces for knowledge to be re-created and amplified by the collective, to acknowledge variation in practice and to negotiate trust. Pathway metaphors represent the object of analysis and the process. A path is an operational tool for executing best practices based upon local practices and clinical guidelines that are shaped by interdisciplinary teams. However, the metaphor is open to different interpretations and convergence but also conflict occur. These occur when different professional boundaries across the thrombectomy landscape are crossed and teams try to map their specific professional identities to enhance flow. Discussion: Pathways can be linked temporarily and conceptually to networks so that their intersections represent points in time-paths where conflicting priorities clash and where interactional expertise from professionals is demanded. The patient's journey is actually a journey through a network of queues, each with its own set of constraints and the thrombectomy pathway within SGH reflects only the micro level of this journey. However, when the pathway trajectories are not linear the 'pathway' narrative becomes more difficult. References: Rotter T, Kinsman L, James EL, Machotta A, Gothe H, Willis J, Snow P, Kugler J. Clinical pathways: Effects on professional practice, patient outcomes, length of stay and hospital costs. Cochrane Database of Systematic Reviews2010;Issue 3:Art. No.: CD006632. doi:10.1002/14651858.CD006632.pub2 Evans MRB, White P, Cowley P, Werring DJ. Revolution in acute ischaemic stroke care: A practical guide to mechanical thrombectomy. Pract Neurol2017;17(4):252–65. Holden RJ, Carayon P, Gurses AP, et al. SEIPS 2.0: A human factors framework for studying and improving the work of healthcare professionals and patients. Ergonomics2013;56(11):1669–86.